2011
DOI: 10.1111/j.1460-9568.2011.07611.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitters couple brain activity to subventricular zone neurogenesis

Abstract: Adult neurogenesis occurs in two privileged microenvironments, the hippocampal subgranular zone of the dentate gyrus and the subventricular zone (SVZ) along the lateral ventricle. This review focuses on accumulating evidence suggesting that the activity of specific brain regions or bodily states influences SVZ cell proliferation and neurogenesis. Neuromodulators such as dopamine and serotonin have been shown to have long-range effects through neuronal projections into the SVZ. Local GABA and glutamate signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 122 publications
0
78
0
1
Order By: Relevance
“…It was proposed that, in addition to their classical role in synaptic transmission, neurotransmitters (NTs) have been proposed to play functional roles both during neurogenesis and during adult life (Buznikov et al, 1996;Biagioni et al, 2002;Karczmar, 2007;Bovetti et al, 2011;Young et al, 2011;Abreu-Villaça et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that, in addition to their classical role in synaptic transmission, neurotransmitters (NTs) have been proposed to play functional roles both during neurogenesis and during adult life (Buznikov et al, 1996;Biagioni et al, 2002;Karczmar, 2007;Bovetti et al, 2011;Young et al, 2011;Abreu-Villaça et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, NTs appear to be "old" molecules that are present in many organisms and that participate in signaling mechanisms that control various cellular functions such as proliferation and migration. Their role in neurogenesis has been proposed on the basis of their early appearance during development, which extends well into the advanced stages of synaptogenesis (Bovetti et al, 2011;Young et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the SVZ is rich in nerve endings originating either from the local neural circuitry, such as medium spiny and aspiny GABAergic neurons of the adjacent striatum (Young et al 2011) or from distant brain regions, such as dopaminergic neurons of the substantia nigra and ventral tegmental area (Hoglinger et al 2004;Baker et al 2004), and serotonergic neurons of the raphe nuclei (Tong et al 2014). g-Aminobutyric acid (GABA) is an inhibitory neurotransmitter and its effect on NS/PCs in the SVZ depends on their source and mode of release but overall it maintains a balance in proliferation and modulates the quiescence of NS/PCs in SVZ (Daynac et al 2013).…”
Section: Niche Innervation and Neurogenesismentioning
confidence: 99%
“…It has been suggested that multiple neurotransmitter systems can affect V–SVZ neurogenesis. 3 However, little is known about the exact source of these neurotransmitters, and the physical and functional interaction between axonal terminals and progenitors or other cells in their niche.…”
mentioning
confidence: 99%
“…3 These include the classical neurotransmitters γ-aminobutyric acid (GABA) 13 and glutamate, which are generally released by presynaptic neurons to directly influence postsynaptic partners, and neuromodulators, such as dopamine, serotonin (5HT), neuropeptide Y, 14 and acetylcholine, which are secreted by a small group of neurons but diffuse through large brain areas to affect a large number of cells. 3 Intriguingly, 5HT-expressing axons are known to project onto the supraependymal surface of the lateral ventricles, 1519 a strategic location that allows the axons direct access to cells exposed to the ventricular cavity. As indicated above, in the walls of the lateral ventricles, E1 cells and B1 cells have apical contacts with the ventricular lumen.…”
mentioning
confidence: 99%